2015
DOI: 10.1126/science.aac6103
|View full text |Cite
|
Sign up to set email alerts
|

Transient assembly of active materials fueled by a chemical reaction

Abstract: Fuel-driven self-assembly of actin filaments and microtubules is a key component of cellular organization. Continuous energy supply maintains these transient biomolecular assemblies far from thermodynamic equilibrium, unlike typical synthetic systems that spontaneously assemble at thermodynamic equilibrium. Here, we report the transient self-assembly of synthetic molecules into active materials, driven by the consumption of a chemical fuel. In these materials, reaction rates and fuel levels, instead of equilib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
702
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 800 publications
(751 citation statements)
references
References 26 publications
5
702
0
6
Order By: Relevance
“…Furthermore, many exciting opportunities in the development of structurally diverse supramolecular polymers can be expected for systems that operate far-from-equilibrium. 40,441 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, many exciting opportunities in the development of structurally diverse supramolecular polymers can be expected for systems that operate far-from-equilibrium. 40,441 …”
Section: Discussionmentioning
confidence: 99%
“…These could be reduced by the addition of what the authors call a chain terminator, a monofunctional (N-methyl)imidazolyl Znporphyrin. In the light of recent developments in manipulating the kinetic stabilities and kinetic pathways in selfassembled supramolecular complexes [128][129][130][131][132][133][134][135][136] and supramolecular polymers, 22,[30][31][32][33][34][35][36][37][38][39][40][41][42]130,[137][138][139][140][141][142][143][144][145] it is interesting to note, that the addition of the chain stopper to the polymers did not lead to instantaneous disassembly. 127 The expected depolymerization and shortening of the polymers based on the comonomer feed ratio was only observed when the di-and monofunctional comonomers were premixed in a good FIGURE 3 (a) Chemical structures for the bi-and monofunctional phosphine ligands, P(Phe) 2 C 12 (Phe) 2 P and P(Phe) 2 C 12 , in order to prepare palladium(II)-based coordination polymers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 We were also particularly interested to apply catalysis to control the rates of certain reactions in the chemical reaction networks driving active soft materials, and to introduce feedback loops. 23,24 4. DESIGN The general design of any molecular system capable of self-assembling after in situ formation of the assembler molecule is based on the following considerations ( Figure 1): 1) the building blocks should all be soluble in the reaction solvent, or should be able to react at a phase boundary; 2) the separate building blocks should not assemble by themselves; 3) the building blocks should carry the functional groups necessary to construct the final covalent bond through a chemical reaction; 4) the final bond forming reaction should be compatible with the conditions (solvent, temperature, concentration, ions, pH) of the self-assembly process, and vice versa.…”
Section: Concept and Motivationmentioning
confidence: 99%
“…However,r ather than just degrading RNA, am ore plausible scenario would embrace recycling, with formation of new 3',5'-bonds through repair of the broken linkages.Atheoretical model addressing this was proposed in 1977 by Usher, [14] who envisioned that day/night alternation on the early earth could have created suitable conditions for the degradation of 2',5'-bonds and subsequent joining of the resulting fragments.H owever,U sher invoked dry-state non-templated oligomerization for the joining chemistry,a nd this is known to only slightly favor the formation of natural linkages [15] and is limited by unfavorable equilibrium considerations to producing short fragments. [16] Furthermore,hydrolysis followed by non-templated synthesis would not allow the propagation of sequence information and, accordingly,w es ought as cheme whereby 2',5'-bonds could be "corrected" to 3',5'-bonds through proofreading with retention of sequence.W er easoned that any such repair process would have an energetic cost, and hence sought an energy-dissipative cycle [17,18] that would combine selective hydrolysis of duplex 2',5'-linkages with templated 3',5'-selective ligation chemistry. [19] We recently reported that templated ligation of mixtures of short oligonucleotides terminating with 2'-a nd 3'-monophosphates can be made 3',5'-selective by means of sequential acetylation and ligation chemistry.T he selectivity derives from preferential 2'-O-acetylation of 3'-monophosphate-terminated oligomers,w hich can then undergo regiospecific ligation.…”
mentioning
confidence: 99%